New injectable antiretroviral therapy for HIV facilitates novel treatment pathways for persons without capacity to consent to medical treatment. (June 2022) - Storrier, Kirbie; Ouliaris, Calina; George, Duncan
Objective: The development of new injectable antiretroviral therapy facilitates treatment for Human immunodeficiency virus (HIV) positive individuals who lack capacity to consent, posing a safety risk to both themselves and the wider community. We consider pathways to enforce treatment and propose an algorithm to determine the most appropriate legal instrument for application. Conclusion: Legislative safeguards in mental health and guardianship legislation provide oversight and protection for those who suffer from illness and require coercive treatment. These frameworks have utility in the treatment of HIV patients who lack capacity to consent to treatment.